Analysis of the Application of Information Technology to Improve the Quality of Public Services - Novia Angelita Margaretha Silitonga; Naya Syaqila Aqla (Asosiasi Penelitian dan Pengajar Ilmu Sosial Indonesia, 2026)
This study aims to analyze the implementation of information technology in improving the quality of public services. The research method used is library research by collecting and analyzing various scientific sources, such as journals, books, research articles, and government documents related to information technology and public services. The results show that the implementation of information technology through online service systems, official websites, and administrative information systems is able to improve the effectiveness, efficiency, transparency, and accessibility of public services. Information technology also helps accelerate administrative processes, reduce data management errors, increase employee productivity, and strengthen communication between the government and the community. In addition, the implementation of information technology supports the realization of e-government and good governance through increased accountability and information transparency. However, the implementation of information technology still faces several challenges, such as limited human resources, inadequate technological infrastructure, unstable internet connections, and the low ability of some communities to use digital services. Therefore, it is necessary to improve employee competencies, develop technological infrastructure, and conduct public socialization to optimize the implementation of information technology in public services. Overall, information technology has proven to be a strategic solution in creating modern, effective, efficient, transparent, and community-oriented public services.